Role of arteriography in rectal hemorrhage due to arteriovenous malformations and diverticulosis. - Talman, E A (1979)
Nine patients with arteriographic right colon arteriovenous malformations (AVM's) are reviewed. Even though five of the eight surviving patients had diverticulosis in remaining colon, right colectomy with removal of the AVM effectively controlled bleeding in seven of the eight patients in follow-up intervals of 14-66 months. Such results suggest that right colon AVM, rather than diverticulosis, may be the more common cause of chronic recurrent lower intestinal hemorrhage in the elderly. Rebleeding occurred in one patient and has heretofore been reported in seven cases. However, since AVM bleeding is rarely life-threatening, right colectomy for chronic recurrent rectal bleeding is justifiable as the initial operative procedure for an AVM, even in the presence of left colon or sigmoid diverticulosis. In the same five year period, 1973-1977, four additional patients with massive hemorrhage, characteristic of diverticulosis, had emergency arteriography with demonstration of a localized site of diverticular bleeding that was controllable by partial colon resection. Consequently, segmental resection of the colon, utilizing selective arteriography, has thus far eliminated bleeding in eight of nine patients with diverticulosis. The judicious use of arteriography in patients with diverticulosis and rectal bleeding substantially reduces the requirement for subtotal colectomy and ileoproctostomy.